Selection of box trap to harvest freshwater prawn (Macrobrachium rosenbergii) from the Sorada reservoir, Odisha: Box trap for catching prawn - Acharya, Priyanka; Das, Nityananda; Khuntia, Basanta Kumar; Nanda, Saumyendra (Journal of the Inland Fisheries Society of India, 2023)
Three types of indigenous box traps, viz. Ghoni, Sepeti and Dori were set in replicates at three different stations of Sorada reservoir in Ganjam District of Odisha. A data set was created by taking the prawn catch information which revealed that catch of prawn started in the month of May and went onwards up to September. The CPUE value for the trap Dori was estimated to be 158.0 g/trap/day for the catch of prawn which was significantly higher than those of two other traps. The study concluded that Dori is a selective gear for catching prawn.